Empowering Island Cultural Resource Education through Generative Artificial Intelligence: Value Logic, Challenges, and Implementation Strategies - , Qiantong Lin; MingLiang Xie; Huaxuan Ye; Hongying Wu; Xinyu Li; Dilin Ruan; Huiling Zhong (International Journal of Education and Humanities, 2025)
The digital era has significantly transformed education and cultural dissemination through Generative Artificial Intelligence (GAI). This technology presents innovative opportunities to optimize Island Cultural Resources (ICR) for education by employing intelligent analysis and personalized recommendations to enrich learning experiences, enhance resource utilization efficiency, and support cultural heritage preservation and innovation. However, GAI also poses challenges alongside its potential, particularly concerning ethics, information security, and academic integrity. This study aims to identify the negative impacts of GAI in education, including the diminishing role and agency of teachers and students, the emergence of information cocoons that limit diverse perspectives, and the growing trend of knowledge homogenization. Additionally, it highlights the urgent need to restructure the educational ecosystem to remain relevant in the face of rapid technological advancements. The research employs a literature review and case study analysis to explore the application of GAI in education, particularly in island-based cultural learning. The findings indicate that GAI may reduce students' creativity and critical thinking without proper implementation while exacerbating digital inequalities. As a recommendation, this study proposes strategies based on human-centric technological ethics, enhanced media literacy, and the deep integration of technology and education to ensure that GAI enriches learning experiences, fosters cultural diversity, and upholds ethical academic values